3
\$\begingroup\$

I have the following function, that I want to minimise using boolean algebra:

$$y = \bar{s} \cdot \bar{u} + s \cdot \bar{u}+s \cdot u$$

Here's my attempt:

$$\bar{s} \cdot \bar{u} + s \cdot \bar{u}+s \cdot u = \bar{u} \cdot (\bar{s} +s)+s \cdot u = \bar{u} \cdot 1+s \cdot u=\bar{u} + s \cdot u = \bar{u} +s$$

In the last step I used the absorption property but I was wondering if there is another way to solve:

$$\bar{u} + s \cdot u$$

\$\endgroup\$

2 Answers 2

5
\$\begingroup\$

Here is how I would solve it.

$$y=s'u' + su' + su $$ $$y=u'(s'+s)+su $$ $$y=u'+su $$ $$y=u'+s $$ Note that I use a slightly different notation, where \$\bar{s}=s' \$.

\$\rule{17cm}{0.4pt} \$ Proof that \$u'+su=u'+s \$

$$u'+su $$ The associative theorem states: \$x+yz = (x+y) \cdot (x+z) \$ $$(u'+u) \cdot (u'+s) $$ $$1 \cdot(u'+s) $$ $$u'+s $$

\$\endgroup\$
1
  • \$\begingroup\$ Ah. It's so clear now. You simply use the associative theorem backwards. Thank you so much! \$\endgroup\$
    – Ski Mask
    Commented Sep 9, 2020 at 14:09
4
\$\begingroup\$

In boolean algebra you can duplicate a term without altering the final result, sometimes this makes things easier to simplify.

$$y = \bar{s} \cdot \bar{u} + s \cdot \bar{u}+s \cdot u$$

We notice that \$s \cdot \bar{u}\$ can be combined with both of the other two terms to produce simpler terms, so we duplicate it.

$$y = \bar{s} \cdot \bar{u} + s \cdot \bar{u}+ s \cdot \bar{u}+s \cdot u$$

$$y = (\bar{s} + s) \cdot \bar{u}+ s \cdot (\bar{u}+ u)$$

$$y = \bar{u}+ s $$

\$\endgroup\$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.